The Influence of Problem Based Learning Model with Flipped Classroom on the Mathematical Literacy Ability of Class VIII Students at SMPN 19 Seluma - Pitriani, Lusi; Muchlis, Effie Efrida; Stiadi, Elwan (Universitas Bengkulu, 2025)
The mathematical literacy of Class VIII at SMP Negeri 19 Seluma is relatively low, as evidenced by the initial literacy test results. This study aims to determine the effect of applying the problem-based learning model with a flipped classroom on the mathematical literacy skills of Class VIII students at SMP Negeri 19 Seluma. This research is a quasi-experimental study using a non-equivalent posttest-only control group design. The population of this study consists of all Class VIII students at SMP Negeri 19 Seluma for the 2023/2024 academic year. The research sample includes Classes VIII A and VIII B, selected using the purposive sampling technique, with the sample consisting of all students in these two classes. The instrument used was a mathematical literacy test sheet with descriptive questions. The results indicate that the average posttest scores of the experimental group were above the completion criteria, while the control group's posttest scores were below the completion criteria. The Mann-Whitney test showed a significant value less than the alpha level (α), or z_count>z_table, leading to the conclusion that there is a significant effect of the problem-based learning model with a flipped classroom on the mathematical literacy skills of Class VIII students at SMP Negeri 19 Seluma.